Eco-friendly Inhibitor (Tribulus terrestris L) for Mild Steel Corrosion in 1 N Phosphoric Acid - SIVARAJU, M.; KANNAN*, K. (Asian Journal of Chemistry, 2024)
The inhibition effect of Tribulus terrestris L alcoholic extract on mild steel corrosion in 1 N phosphoric acid has been studied by mass loss and polarization techniques between 303 and 333 K. The inhibition efficiency increased with increase in concentration of plant extract. The corrosion rate increased with increase in temperature and decreased with increase in concentration of inhibitor compared to blank. The adsorption of inhibitor on mild steel surface has been found to obey Temkin's adsorption isotherm. Potentiostatic polarization results revealed that Tribulus terrestris L extract act as mixed type inhibitor. The values of activation energy (Ea), free energy of adsorption (ΔGads), heat of adsorption (Qads), enthalpy of adsorption (ΔH) and entropy of adsorption (ΔS) were calculated. Surface analysis (FT-IR and SEM) was also carried out to establish the mechanism of corrosion inhibitor on mild steel corro-sion in phosphoric acid medium.